Pengaruh Kepuasan Kerja terhadap Komitmen Organisasional Karyawan pada Organisasi Kantor Hukum - Priskilla Nahita; Eva Hotnaidah Saragih (Research Center and Case Clearing House PPM School of Management, 2021)
From the literature studies, research has not been found that examines the effect of job satisfaction on employee commitment in organizations engaged in law firms, especially in the context of Jakarta, Indonesia. Generally, research is carried out in business organizations or government organizations. Meanwhile, managing a law office is different from managing a business or government organization. It is necessary to know how best an organization in the legal field should manage and treat its employees, so that they have high satisfaction and commitment to achieving organizational goals. Whether the approach to human resource management should be the same or different from that applied to other types of organizations. Thus this study aims to: (1) quantitatively examine the effect of job satisfaction on employee commitment in organizations engaged in the Law Office, (2) Identify the level of job satisfaction and employee commitment to the Law Office organization which is the object of study and the factors dominant forms of job satisfaction and high commitment from employees, and (3) Establishing theoretical and managerial implications based on the findings obtained in the first and second research objectives. The research was conducted using quantitative research methods through simple regression analysis. The data collection technique was carried out by distributing questionnaires to 153 (one hundred and fiftythree) respondents from a law office located in Jakarta, Indonesia. The results showed that job satisfaction had a significant positive effect on employee organizational commitment. This study also found three dimensions of job satisfaction that received high ratings so that the overall job satisfaction rate was categorized as very good. The four dimensions are sequentially: appreciation from the company, colleagues and the nature of the job.